EFFICIENCY OF ALTERNATIVE THERAPY APPROACHES FOR THE CHILDREN - A.A. Baranov; L.S. Namazova (Педиатрическая фармакология)
The article deals with the information on opportunities to apply «unconventional» approaches (alternative therapy) with the specific stress on the validity of recommendations for these types of treatment provided for the patients, suffering from allergy, asthma and recurrent respiratory infections.Key words: phytotherapy, alternative medicine, treatment, bronchial asthma.